PENGARUH MODEL COOPERATIVE LEARNING TIPE JIGSAW DAN TEAMS GAMES TOURNAMENT TERHADAP PENINGKATAN BERPIKIR KRITIS PENDIDIKAN PANCASILA KELAS IV SEKOLAH DASAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this research is the low critical thinking ability of fourth-grade students at SD Negeri 1 Metro Utara. The objective of this research is to describe and analyze the influence of the cooperative learning model types Jigsaw and Teams Games Tournament on the improvement of critical thinking among fourth-grade elementary school students, and to determine the difference in the improvement of critical thinking using the Jigsaw model and the Teams Games Tournament model. This research is quantitative in type, using a quasi-experimental method. The research design used is a non-equivalent control group. The sampling technique employed is non-probability sampling with purposive sampling. The population used in this research is all fourth-grade classes at SD Negeri 1 Metro Utara. The research samples are: IVA class as the experimental class, IVB class as the control class, and IVC class as the instrument testing class. The total sample for IVA and IVB classes is 58 students. The data collection technique uses test and non-test methods. The data analysis technique uses simple linear regression testing and independent sample T-test. The research results show a significant influence on the cooperative learning model type Jigsaw, with a calculated F-value of 243,498 > F-table of 4.19, while for the Teams Games Tournament model, the calculated F-value is 55,709 > F-table of 4.19. There is a significant difference between the models, as indicated by a calculated t-value of 0.010 < t-table of 0.05.